Quantifying spatial accessibility to inpatient hospices in Germany - Theresa Petzold; Friedemann Nauck; Christian Banse; Jobst Augustin; Birgit Jaspers; Maximiliane Jansky (BMC Health Services Research, 2026)
Abstract Background Spatial access is an important indicator to assess quality of healthcare services and healthcare situation, with accessibility and availability as central components. Using inpatient hospices as an example of specialist palliative care in Germany, different indicators are used to measure spatial accessibility, which vary in complexity and considered variables. We compare four widely used methods, identify regional differences, and discuss possible differences in the results caused by methodological characteristics. Methods Locations of inpatient hospices were identified using a freely accessible online self-disclosure database, supplemented by lists from regional associations and own research. Spatial access was examined using provider-to-population ratios based on district level, and network-based travel time of 15, 30 and 60 min as used in literature. Further, Two-Step Floating Catchment Area (2SFCA) and Enhanced Two-Step Floating Catchment Area (E2SFCA) were applied using geocoded locations, hospice bed capacities, population data, and road network data. Results 295 inpatient hospices were identified. 211 of 401 districts have at least one hospice, resulting in an availability of 36.4 beds per 1 million inhabitants nationally. 90.3% of the population can reach a hospice by car within 30 min (network-based travel time). The results of the FCA methods show a heterogeneous pattern in spatial accessibility index (SPAI i ). Using 2SFCA method results in uniform accessibility within the catchment areas of the hospices. While E2SFCA method with a slow distance decay function generates smoother transition zones within catchment areas, the sharp distance decay function induces higher spatial differentiation, particularly in rural areas, where accessibility declines sharply with distance. Conclusions The results indicate that inpatient hospices in Germany are timely accessible via private transport, if available, though rural areas have lower accessibility. However, the chosen method significantly influences the results. Indicators such as provider-to-population ratios and network-based travel time can provide a basic analysis of the care situation due to their ease of interpretation. This study can raise awareness among decision-makers planning new hospices to consider more advanced methods, such as FCA methods, as these take both dimensions of accessibility equally into account.